2008
DOI: 10.1063/1.3050452
|View full text |Cite
|
Sign up to set email alerts
|

Lithium salt doped conjugated polymers as electron transporting materials for highly efficient blue polymer light-emitting diodes

Abstract: Highly efficient blue polymer light-emitting diodes (PLEDs) are fabricated using a conjugated polymer, poly[9,9-bis(2-(2-(2-diethanol-amino-ethoxy) ethoxy) ethyl) fluorene-alt-4, 4′-phenylether] as an electron transporting layer (ETL). It was found that the performance of these blue-emitting devices could be greatly improved if the ETL was doped with LiF or Li2CO3 salts. A bis[(4,6-di-fluorophenyl)-pyridinato-N, C2] (picolinate) Ir(III) (FIrpic) complex based blue phosphorescent PLED exhibited a maximum lumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…While using iridium(III) [bis(4,6-difluorophenyl)pyridinato-N,C 2 ]picolinate (FIrpic) as the dopant, the maximum power efficiency (PE) only reaches 0.8 lm/W [62]. By blending PVK with electron-transport materials, major improvements could however be achieved and blue PLEDs with peak current efficiencies ranging between 15 and 24 cd/A were obtained [82,[89][90][91][92]. Extending these results to other emission colors proved to be a less challenging task.…”
Section: Pvk a Best Seller As Polymeric Hostmentioning
confidence: 98%
“…While using iridium(III) [bis(4,6-difluorophenyl)pyridinato-N,C 2 ]picolinate (FIrpic) as the dopant, the maximum power efficiency (PE) only reaches 0.8 lm/W [62]. By blending PVK with electron-transport materials, major improvements could however be achieved and blue PLEDs with peak current efficiencies ranging between 15 and 24 cd/A were obtained [82,[89][90][91][92]. Extending these results to other emission colors proved to be a less challenging task.…”
Section: Pvk a Best Seller As Polymeric Hostmentioning
confidence: 98%
“…
Phosphorescent polymer light-emitting diodes (PPLEDs), in which the triplet emitters are dispersed into the polymeric hosts via physical blending [1][2][3][4][5][6] or chemical bonding, [7][8][9][10][11][12] have attracted much attention because of their low-cost preparation from solution either by spin-coating or via inkjet printing as well as the capability to harness both the singlet and triplet excitons to realize theoretical 100% internal quantum efficiency. [13][14][15] For solid-state lighting applications, the development of power-efficient blue, green and red PPLEDs is essential.
…”
mentioning
confidence: 99%
“…Due to a suppressed phosphorescent quenching by using PVK as the anode buffer layer, a high LE of 26.4 cd A À1 , which is one of the best results based on conjugated polymer reported to date [11][12][13][14][15][16][17] was achieved. More importantly, as compared with the devices based on the non-conjugated host polymer PVK, the devices based on polyfluorene host showed a lower turn-on voltage (3.6 V vs. 4.4 V) and higher PE (17 lm W À1 vs. 8.3 lm W À1 ).…”
Section: Introductionmentioning
confidence: 87%
“…The obtained devices showed a maximal luminous efficiency (LE) of 18.2 cd A À1 and power efficiency (PE) of 8.8 lm W À1 , respectively [12]. Huang et al reported that by using Li 2 CO 3 -doped poly [9,9-bis(2-(2-(2-diethanol-aminoethoxy) ethoxy) ethyl) fluorene-alt-4, 4 0 -phenylether] (PDFPE) as the electron transporting layer and p-doped poly (3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) (PEDOT:PSS) as hole transporting layer, blue-emitting phosphorescent PLEDs based on PVK: FIrpic exhibited a maximal LE of 20.3 cd A À1 and PE of 9.2 lm W À1 [13]. With similar strategy, the efficiency of the blue-emitting phosphorescent PLEDs from PVK: FIrpic have been improved to 22-28 cd A À1 , via doping the active layer with electron transporting molecules or incorporation of small-molecule based electron-transport layer [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%